NetConfer: a web application for comparative analysis of multiple biological networks (vol 18, 53, 2020) - Nagpal, Sunil; Das Baksi, Krishanu; Kuntal, Bhusan K.; Mande, Sharmila S. (BMC Biology, 2020)
An amendment to this paper has been published and can be accessed via the original article.

NetConfer: a web application for comparative analysis of multiple biological networks - Nagpal, Sunil; Baksi, Krishanu Das; Kuntal, Bhusan K.; Mande, Sharmila S. (BMC Biology, 2020)
Background Most biological experiments are inherently designed to compare changes or transitions of state between conditions of interest. The advancements in data intensive research have in particular elevated the need for resources and tools enabling comparative analysis of biological data. The complexity of biological systems and the interactions of their various components, such as genes, proteins, taxa, and metabolites, have been inferred, represented, and visualized via graph theory-based networks. Comparisons of multiple networks can help in identifying variations across different biological systems, thereby providing additional insights. However, while a number of online and stand-alone tools exist for generating, analyzing, and visualizing individual biological networks, the utility to batch process and comprehensively compare multiple networks is limited. Results Here, we present a graphical user interface (GUI)-based web application which implements multiple network comparison methodologies and presents them in the form of organized analysis workflows. Dedicated comparative visualization modules are provided to the end-users for obtaining easy to comprehend, insightful, and meaningful comparisons of various biological networks. We demonstrate the utility and power of our tool using publicly available microbial and gene expression data. Conclusion NetConfer tool is developed keeping in mind the requirements of researchers working in the field of biological data analysis with limited programming expertise. It is also expected to be useful for advanced users from biological as well as other domains (working with association networks), benefiting from provided ready-made workflows, as they allow to focus directly on the results without worrying about the implementation. While the web version allows using this application without installation and dependency requirements, a stand-alone version has also been supplemented to accommodate the offline requirement of processing large networks.
Keywords: Bioinformatics; biological networks; Interaction networks; Network comparison; visualization